Remoção de níquel de soluções aquosas em batelada e em coluna utilizando a alga marinha marrom Sargassum filipendula - DOI: 10.4025/actascitechnol.v29i2.695 - Seolatto, Araceli Aparecida; Veit, Márcia Terezinha; Cossich, Eneida Sala; Tavares, Célia Regina Granhen; Silva, Edson Antônio da; Pontel, Eduardo Augusto (Acta Scientiarum. Technology, 2008)
The nickel(II) biosorption capacity of the Sargassum filipendula brown marine algae was studied in the batch mode. The biosorption study involved the determination of equilibrium data of the nickel-biomass system, considering the influence of the pretreatment, particle size and agitation speed on the biosorption process. The equilibrium data obtained for the batch and column systems were adjusted by means of the Langmuir isotherm. The results showed that the column system presents a larger capacity of nickel removal from the aqueous solutions, compared to the batch system. The biosorption equilibrium was obtained in approximately four hours of experiment. The biomass size, agitation speed and the pre-treatment of algae did not affect nickel biosorption rate and biosorption capacity.